Порівняльний аналіз розподілу тиску природного газу у похилому та горизонтальному трубопроводі - Лесовой, Леонід; Близняк, Леся (Видавництво Національного університету «Львівська політехніка», 2002)
The benchmark analysis of calculating of pressure distribution of natural gas in tilted conduits and horizontal conduit is made. Calculating relative inaccuracy in the event of tilted under its ascent and downwards is made.